LEMBAGA PENDIDIKAN ISLAM AKHIR ABAD XX Studi Pendidikan Muhammadiyah Sekolah Umum Plus dan Boarding School - Listiana, Heni (State Islamic Institute of Madura, 2015)
Abstract: Modernization of Islamic education institutions in Indonesia was preceded by Muhammadiyah movement that rised the idea of extra public schools or so called